New-Paradigm Research in Medicine: An Agenda - Levin, Jeff (Journal of Scientific Exploration, 2017)
Critics of Western medicine have long heralded a “new paradigm” opposed to the reigning materialistic worldview of biomedical science and allopathy. This new paradigm has undergone several name changes (e.g., holistic, alternative, complementary, integrative) and presumably advances a radically new worldview. On closer inspection, it looks more like the opposite pole of the same dualistic worldview and not a radical break with the past. A truly new paradigm prepared to jettison tacit conceptual assumptions would have significant implications for medical research, provided that institutional and professional constraints not inhibit the studies to follow. A research agenda is proposed comprising possible jumping-off points for investigators comfortable with working around the reigning assumptions both of current medical thinking and of a rapidly institutionalizing integrative-medicine worldview. These include proposed medical research on spirituality, alien abductions, hierophanies, thought forms, placebo pharmacology, radionics, arcane medical wisdom, prenatal ensoulment, and musical genetics.